2014
DOI: 10.1016/j.jped.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Pediatric Index of Mortality 2 in pediatric patients with complex chronic conditions

Abstract: PIM2 showed poor performance in patients with CCCs and in the general population. This result may be secondary to differences in the characteristics between the study samples (high prevalence of patients with CCCs); the performance of the PIM2 should not be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In contrast to other studies that indicate a relationship between functional status at discharge, assessed by the Pediatric Cerebral Performance Category (PCPC) and the Pediatric Outcome Performance Category (POPC), and predictive mortality rates at admission, ( 5 , 14 , 15 ) in this study, we did not observe a significant difference in admission PIM2 values, according to the impairment in the overall FSS score presented by individuals at discharge from the PICU . This can be explained by Fonseca et al, ( 16 ) who verified that the PIM2 proved to be an inadequate measure to predict the mortality of patients with chronic conditions, which seems to be the case of the population in our study, in which only 16% individuals did not present any health condition prior to hospitalization in the PICU. The authors note the inclusion of few prediction variables to assess these conditions as a limitation of the PIM2, ( 16 ) in addition to considering only the first hour of patient hospitalization, as clinical conditions can vary dramatically within the first 24 hours of hospitalization.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In contrast to other studies that indicate a relationship between functional status at discharge, assessed by the Pediatric Cerebral Performance Category (PCPC) and the Pediatric Outcome Performance Category (POPC), and predictive mortality rates at admission, ( 5 , 14 , 15 ) in this study, we did not observe a significant difference in admission PIM2 values, according to the impairment in the overall FSS score presented by individuals at discharge from the PICU . This can be explained by Fonseca et al, ( 16 ) who verified that the PIM2 proved to be an inadequate measure to predict the mortality of patients with chronic conditions, which seems to be the case of the population in our study, in which only 16% individuals did not present any health condition prior to hospitalization in the PICU. The authors note the inclusion of few prediction variables to assess these conditions as a limitation of the PIM2, ( 16 ) in addition to considering only the first hour of patient hospitalization, as clinical conditions can vary dramatically within the first 24 hours of hospitalization.…”
Section: Discussionmentioning
confidence: 51%
“…This can be explained by Fonseca et al, ( 16 ) who verified that the PIM2 proved to be an inadequate measure to predict the mortality of patients with chronic conditions, which seems to be the case of the population in our study, in which only 16% individuals did not present any health condition prior to hospitalization in the PICU. The authors note the inclusion of few prediction variables to assess these conditions as a limitation of the PIM2, ( 16 ) in addition to considering only the first hour of patient hospitalization, as clinical conditions can vary dramatically within the first 24 hours of hospitalization. ( 17 )…”
Section: Discussionmentioning
confidence: 51%
“…After adjusting for illness severity, various studies have reported that having an increasing number of chronic conditions was associated with increasing odds of mortality 11 19 22 25. Fonseca and Ferreira26 reported the performance of PIM2 with chronic conditions in Brazil and found that the increased mortality of patients with chronic conditions could not be verified by the probability of death estimated by PIM2. The similar probabilities between patients with and without chronic conditions may indicate poor score performances 26.…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca and Ferreira26 reported the performance of PIM2 with chronic conditions in Brazil and found that the increased mortality of patients with chronic conditions could not be verified by the probability of death estimated by PIM2. The similar probabilities between patients with and without chronic conditions may indicate poor score performances 26. Edwards et al 11 also reported that patients with chronic conditions had significantly higher risks of mortality in the PICU than that predicted by PIM2 11…”
Section: Discussionmentioning
confidence: 99%
“…The classification system has also been used to support the development of study measures: illness severity and multimorbidity (Keele, Keenan, Sheetz, & Bratton, 2013; Lindley, 2017; Lindley & Keim-Malpass, 2017). Finally, the system has been utilized in the development of pediatric indices (daFonseca & Ferreira, 2014). Thus, the original CCC classification system is considered the gold standard in identifying children with life-limiting illness.…”
Section: Classification Systems Of Pediatric Complex Chronis Conditionsmentioning
confidence: 99%